Smart concrete: an illustration through a smart concrete chess game of potential applications in construction 4.0. (19th April 2021) - Amghar, Bilal; Mansoutre, Sandrine; Colin, Johan; Florence, Celine; Brito, Artur De Morais
Abstract: The global performance of a structure or a system can be improved during the process of its construction or operation or end of life, with multifunction and connected elements. Concrete presents several benefits for being used in this way, in particular with integrated electronic systems. This paper deals with smart concrete through a small size example, a chess game, i.e. board and pawns, to illustrate the potential applications on a larger scale in the field of construction. Different kind of sensors can be used in concrete construction. After comparing the advantages and disadvantages of each, magnetic sensors have been chosen to equip the concrete chessboard, handcrafted in the present work. The concrete used is UHPC (Ultra high performance concrete fiber reinforced or not), a new type of concrete with special properties, for the benefits of its mechanical strength and deformation, self-levelling workability and aesthetic surface rendering. Chess pawns and chess board have been cast with a specific protocol to embed the magnets and the sensor inside the concrete, by taking into account both its flocculation and setting times. Results of the tests show the feasibility to use magnetic sensors in concrete systems and show a good transmission of the magnetic signal through the concrete, which is very promising for further development of new concrete smart systems, that are easy and rentable to implement. The permeability of concrete to magnetic fields, robustness and sensitivity of sensor are the advantages of this application.